Bidens pilosa (Black Jack) Standardized Extract Ameliorates Acute TNBS-induced Intestinal Inflammation in Rats - Quaglio, Ana E.V.; Cruz, Vinicius M.; Almeida-Junior, Luiz D.; Costa, Celso A.R.A.; Di Stasi, Luiz C. (Planta Medica, 2020)
Bidens pilosa is an herb popularly used to treat inflammation, hemorrhoids, fever, and gastric ulcers with reported pharmacological activities and chemical composition that sustain its selection as a potential intestinal anti-inflammatory product. Based on this, we examined the effects of a B. pilosa fatty acid-standardized supercritical preparation on the intestinal inflammatory process induced by trinitrobenzenesulphonic acid in rats, using either preventative or curative treatments. We also investigated the safety of plant extract by acute and sub-chronic toxicological analysis. The intestinal anti-inflammatory activity was related to modulation of the immune response, increasing IL-10 production and reducing IL-1β, IL-6, and TNF-α level, the oxidative stress, and the MUC production in the inflamed colon. Optic, scanning, and transmission electron microscopy (TEM) analysis supported the beneficial effects promoted by B. pilosa, which were closely related to downregulation of heparanase, Hsp70, Mapk 3, and NF-κB signaling and with the presence of long-chain fatty acids in extract. Our data suggest that B. pilosa supercritical preparation is a chemically standardized preparation potentially useful as complementary intestinal anti-inflammatory agent to treat inflammatory bowel disease.
Keywords: IBD; Bidens pilosa; Asteraceae; cytokines; mucins; oxidative stress; immune modulation